Bactericidal Activity of N-Chlorotaurine against Biofilm-Forming Bacteria Grown on Metal Disks - Coraça-Huber, Débora C. (American Society for Microbiology, 2014)
Many orthopedic surgeons consider surgical irrigation and debridement with prosthesis retention as a treatment option for postoperative infections. Usually, saline solution with no added antimicrobial agent is used for irrigation. We investigated the activity of N-chlorotaurine (NCT) against various biofilm-forming bacteria in vitro and thereby gained significant information on its usability as a soluble and well-tolerated active chlorine compound in orthopedic surgery. Biofilms of Staphylococcus aureus were grown on metal alloy disks and in polystyrene dishes for 48 h. Subsequently, they were incubated for 15 min to 7 h in buffered solutions containing therapeutically applicable concentrations of NCT (1%, 0.5%, and 0.1%; 5.5 to 55 mM) at 37°C. NCT inactivated the biofilm in a time- and dose-dependent manner. Scanning electron microscopy revealed disturbance of the biofilm architecture by rupture of the extracellular matrix. Assays with reduction of carboxanilide (XTT) showed inhibition of the metabolism of the bacteria in biofilms. Quantitative cultures confirmed killing of S. aureus, Staphylococcus epidermidis, and Pseudomonas aeruginosa biofilms on metal alloy disks by NCT. Clinical isolates were slightly more resistant than ATCC type strains, but counts of CFU were reduced at least 10-fold by 1% NCT within 15 min in all cases. NCT showed microbicidal activity against various bacterial strains in biofilms. Whether this can be transferred to the clinical situation should be the aim of future studies.